Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Research perspectives and micropropagation of Cardioteucris cordifolia C. Y. Wu - Mu Ze; Binyue Zhang; Haoyu Ma; Zhun Sun; Ming Dong; Lijuan Zou (In Vitro Cellular & Developmental Biology - Plant, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

The Complete Mitochondrial Genome of a Newly Recorded Chinese Species of Diglyphus sabulosus (Hymenoptera: Eulophidae) and Insights into Its Phylogenetic Position - Lu-Chao Fang; Zhi-Qiang Ge; Ou-Yan Xi; Ze-Lu Mu; Hong-Ying Hu (Biochemical Genetics, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

A robust system for somatic embryogenesis and shoot organogenesis in Begonia grandis subsp. sinensis (A. DC.) Irmsch and genetic fidelity assessment of the regenerants - Feimin Ma; Zhengli Shan; Haonan Su; Ruijing Han; Wenjing Zhou; Mu Ze; Ming Dong; Qinggui Wu; Lijuan Zou (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Discovery of novel nuciferine-based URAT1 inhibitors for hyperuricemia: synthesis, biological evaluation, and computational insights - Yan-fei Liu; Ze-sheng Hao; Xu Guo; Shu-tao Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Jin-yue Sun; Chao Liu (Medicinal Chemistry Research, 2026)

Synergistic construction of an annual 2 m mangrove species dataset from 2016 to 2023 using structural features and hybrid stacked deep learning models—Beibu Gulf, Guangxi, China - Jun Sun; Weiguo Jiang; Ziyan Ling; Bolin Fu; Ze Zhang; Zhijie Xiao; Xingling Mu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Physiological and transcriptomic response reveals new insight into manganese tolerance of Celosia argentea Linn. - Liyun Liang; Mu Ze; Jun Yang; Qian Xu; Cunmei Du; Xiaohong Hu; Ming Dong; Lijuan Zou; Tuo Qi (Journal of Hazardous Materials, 2024)

Unsymmetric design of self-supported sheet electrode: Breaking the tradeoff between electrical conduction and surface wetting for fast energy storage and excellent cycling stability - Bin Zhang; Ze Zhang; Yuefeng Qiu; Zhiheng Wang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2024)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Association between urinary cadmium level and subclinical myocardial injury in the general population without cardiovascular disease aged ≥ 50 years - Yu-Jie Wu; Si-Bo Wang; Jia-Teng Sun; Ling-Feng Gu; Ze-Mu Wang; Bo Deng; Hao Wang; Lian-Sheng Wang (Environmental Science and Pollution Research, 2023)

Quantitative Determination of Trace Lipopeptide Using HPLC through Double Carboxyls Labelling - Shi-Zhong Yang; Hong-Zhi Quan; Jin-Feng Liu; Hong-Ze Gang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2020)

Performance, kinetics characteristics and enhancement mechanisms in anammox process under Fe(II) enhanced conditions - Si-min Tang; Ze-hao Xu; Ya-lei Liu; Guang-feng Yang; Jun Mu; Ren-cun Jin; Qiao Yang; Xiao-ling Zhang (Biodegradation, 2020)

Genetic mapping of powdery mildew resistance genes in soybean by high-throughput genome-wide sequencing - Bingzhi Jiang; Mu Li; Yanbo Cheng; Zhandong Cai; Qibin Ma; Ze Jiang; Ruirui Ma; Qiuju Xia; Gengyun Zhang; Hai Nian (Theoretical and Applied Genetics, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)